Rapid Curing Epoxy Resin and Its Application in Carbon Fibre Composite Fabricated Using Vartm Moulding. Issue 5 (June 2013) - Wang, C.R.; Gu, Y.Z.; Zhang, K.M.; Li, M.; Zhang, Z.G.
A rapid curing resin system made from the diglycidyl ether of bisphenol A epoxy, modified imidazole and modified aliphatic amine was developed. The curing behaviour and following characteristic of the resin were evaluated by differential scanning calorimetric and rheological analysis, respectively. Carbon fibre-reinforced polymer composite (CFRP) laminates using this resin system were manufactured through vacuum-assisted resin transfer moulding (VARTM) under short-term curing schedule. Subsequently, studies were performed on the processing quality, mechanical properties and heat resistance of the composites. The effects of post-cure duration on the interfacial bonding and the properties of the composites were investigated. The results showed that the curing time of a CFRP laminate using the studied resin under 120 °C could be controlled within 13 min with more than 95% curing degree and few defects. There were variations of the mechanical and thermal properties of the composites with different post-cure durations. The optimum properties were obtained after a post-cure process of 60 min, and extended post-cure treatment were detrimental. The corresponding mechanism was discussed from the viewpoint of interfacial bonding between carbon fibre and epoxy matrix.